2013
DOI: 10.1007/s11010-013-1624-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial Bax, caspases, and MAPKs for ceramide-induced apoptosis in renal proximal tubular cells

Abstract: It remains elusive whether crosstalk exists among mitochondrial Bax, caspases, and mitogen-activated protein kinases (MAPKs), and whether epidermal growth factor (EGF), which may activate MAPKs, affects ceramide-induced apoptosis through the crosstalk in renal proximal tubular cells (RPTCs). Effect of ceramide on expression of mitochondrial Bax and phosphorylated (p)-ERK, p38MAPK and JNK, that of MAPKs inhibition, and of EGF in the presence or absence of MAPKs inhibition on ceramide-induced apoptosis were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Apoptosis and necrosis of tubular cells have been considered as the major consequences of cisplatin-induced AKI (6,10,36). Human AD-MSCs have been shown to exhibit antiapoptotic capacity in vivo (23,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis and necrosis of tubular cells have been considered as the major consequences of cisplatin-induced AKI (6,10,36). Human AD-MSCs have been shown to exhibit antiapoptotic capacity in vivo (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…BAX and Bcl-2 are two key regulators (proapoptotic and antiapoptotic, respectively) of apoptosis. Previous studies have demonstrated that MSC engraftment downregulates the expression level of BAX, but upregulates the expression level of Bcl-2 in kidneys with AKI, which modulates their expression back to a control level (13,23,36). In the current in vitro co-culture system, the expression patterns of three key regulators (p38, BAX and Bcl-2) of apoptosis were clearly demonstrated following AD-MSC treatment, which was an important addition to the in vivo data demonstrating that AD-MSCs are able to effectively regulate apoptotic proteins (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies show that ceramide is accumulated in kidneys exposed to anti-glomerular membrane (GBM) antibody [ 52 ], nephrotoxins such as carbon tetrachloride [ 67 ] and isoflurane [ 62 ], developing kidney [ 68 , 69 ], ischemia/reperfusion (I/R) injury [ 51 , 52 ], glycerol-induced myohemoglobinuria [ 52 ], and obstructive nephropathy [ 70 ]. These stimuli can induce apoptosis, and an apoptogenic role of ceramide is further supported by the ability of exogenous ceramide to induce apoptosis in RTCs [ 50 , 63 , 68 , 71 ].…”
Section: Ceramide-induced Apoptosismentioning
confidence: 99%
“…Conversely, the phosphorylation of these kinases was enhanced in IGFBP5 knockdown cells, which was confirmed by Western blot and RT-PCR analyses. In addition, the activity of ERK pathway associated proteins, such as Bax (Iwayama and Ueda, 2013; Ma et al, 2014; Yating et al, 2015) and caspase-3 (Sudo and Minami, 2011; Wang et al, 2011), and the downregulation of antiapoptotic proteins, such as Bcl2 (Mebratu and Tesfaigzi, 2009; Roskoski, 2012; Sudo and Minami, 2010), is associated with the upregulation of apoptosis execution. Our results obtained from the qRT-PCR and Western blot analyses indicated that the Bax and caspase-3 levels were significantly increased, while the level of Bcl2 was significantly decreased in the IGFBP5-shRNA group.…”
Section: Discussionmentioning
confidence: 99%